2010
DOI: 10.4314/ajfand.v10i2.53356
|View full text |Cite
|
Sign up to set email alerts
|

Fruit yield and quality of drip-irrigated tomato under deficit irrigation

Abstract: The competition for limited amount of world fresh water is increasing at a fast rate. The agricultural sector is the major water user and also the most inefficient. As a result, the economic return from a unit of water is the lowest for agricultural sector. Therefore, in the wake of dwindling water availability, it is becoming imperative to look for ways of maximizing yield and quality of produce per unit of water. This is especially important in countries like Ethiopia, where there is severe water shortage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 21 publications
14
43
0
4
Order By: Relevance
“…However, the available literature presents some discrepancies, linked to the cultivars used and/or to the phenological period of application of deficit irrigation treatments [7]. Moreover, most of these studies are in greenhouses or under controlled conditions [27][28][29][30][31][32][33][34]. Notwithstanding, there is still little understanding on the mechanisms of PRD in different tomato cultivars grown under open field conditions, and any agro-climatic parameters (e.g., air temperature) can influence the plant response.…”
Section: Introductionmentioning
confidence: 99%
“…However, the available literature presents some discrepancies, linked to the cultivars used and/or to the phenological period of application of deficit irrigation treatments [7]. Moreover, most of these studies are in greenhouses or under controlled conditions [27][28][29][30][31][32][33][34]. Notwithstanding, there is still little understanding on the mechanisms of PRD in different tomato cultivars grown under open field conditions, and any agro-climatic parameters (e.g., air temperature) can influence the plant response.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in yield and its components with increasing water stress levels in this study was consistent with the findings of previous studies. Birhanu & Tilahun (2010) and Zhang et al (2016) found a reduction in the weight and quantity of fruits in plants exposed to water stress. Water stress reduces the number of fruits and flowers, and fruit set percentage of a plant (Pek et al, 2014).…”
Section: Fruit Yield and Its Componentsmentioning
confidence: 99%
“…Wahb-Allah and Al-Omran [14] reported as negative effect of deficit irrigation was more obvious when coupled with salt stress and concerning crop developmental stage it was indicated as fruiting and vegetative growth stages were the most tolerant to deficit irrigation whereas, the reproductive stage was the most sensitive one Application of deficit irrigation in crop production is an approach to save water in areas of water shortage and longer drought during production period so as to maximize water productivity. Regulated deficit irrigation saves substantial amount of irrigation water and increases water use efficiency quoted [19,20]. Besides, deficit irrigation reduces production costs, conserves water and minimizes leaching of nutrients and pesticides in to ground water [21] and mostly practiced in areas where water scarcity exists.…”
Section: Effect Of Deficit Irrigation On Tomato Yield and Qualitymentioning
confidence: 99%
“…The authors included as total soluble content was increased with stress level and varies among cultivars while the fruit water content was decreased: Melkassa Marglobe cultivar had higher total soluble solute content than Melka Shola cultivar and the higher total soluble solute content of Melkassa Marglobe might be the reason why this cultivar is preferred by consumers for use as a salad [19].…”
Section: Effect Of Deficit Irrigation On Tomato Yield and Qualitymentioning
confidence: 99%